Screening of Antiradical and Antibacterial Activities of Essential Oils of Artemisia campestris L., Artemisia herba alba Asso, & Thymus capitatus Hoff. Et Link. Growing Wild in the Southern of Tunisia - Amouri, Mohamed Neffati, Ahmed Akrout, Hajer El Jani, Sondes (Recent Research in Science and Technology, 2009)
The present study was conducted to evaluate in vitro antibacterial and antiradical activities of essential oils extracted from air-dried leaves of Artemisia campestris Artemisia herba alba and Thymus capitatus growing wild in the southern of Tunisia. The principle compounds of Artemisia campestris oil were b-pinene (45.8%) and a-pinÃƒÂ¨ne (12.5%), the major constituents of Artemisia herba alba oil were ÃŽÂ²-thujone (30.0%) and ÃŽÂ±-thujone (25.7%) whereas the Thymus capitatus oil was mainly composed of Ã‚Â carvacrol (68.8%) and p-cymÃƒÂ¨ne (11.1%). The determination of the antiradical activity by DPPH method showed that Thymus capitatus oil exerted the highest activity with (0.15 Ã‚Âµl/ml), followed by Artemisia herba alba (1.0 Ã‚Âµl/ml) and Artemisia campestris (2.09 Ã‚Âµl/ml). The screening of the antibacterial activity against seven bacteria using the disc diffusion method showed that Thymus capitatus oil strongly inhibited the growth of all bacteria studied (20 - 30 mm) except Pseudomonas aerogunosa which was resistant to all oils. The two other oils exhibited moderate and weak antibacterial activity. These results show and confirm that Thymus capitatus possesses strong antiradical and antibacterial activities, and therefore it could be used as a natural preservative ingredient in food and/or pharmaceutical industries.